Crop Returns, Human Employment and Resource use Productivity on Bullock and Tractor Farms in Upper Luni Basin (W. Rajasthan) - Sharma, D B.S; Purohit, M L (Annals of Arid Zone, 2016)
Bullock and tractor operated farms were surveyed and data analysed for crop returns, human employment and resource use productivity in Upper Luni Basin (western Rajasthan). Percentage of gross cropped area under cereals and pulses was found different On two types of farms. Per hectare crop income was more on irrigated and unirrigated tractor farms as compared to bullock farms.Â· About ten per cent decrease in human employment was noted due to tractorization. There is scope of increasing tractor and human employment on tractor-farms and use uf manure and fertilizers on bullock farms.